2019
DOI: 10.14336/ad.2019.0121
|View full text |Cite
|
Sign up to set email alerts
|

Disability Transitions and Health Expectancies among Elderly People Aged 65 Years and Over in China: A Nationwide Longitudinal Study

Abstract: Disability has become a critical issue among elderly populations, yet limited large-scale research related to this issue has been conducted in China, an aging society. This study explored sex and urban-rural differences in disability transitions and life expectancies among older adults in China. Data were collected from the Chinese Longitudinal Health Longevity Survey (CLHLS), which enrolled people aged 65 and older and was conducted in randomly selected counties and cities across 22 provinces in China. Disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…The older people with FL were limited on physical activities, increasing the risk of disabled IADL, which greatly reduced the health status of the older people. IADL is an important indicator that affects health, but its impact on the health or death of the older people is often overlooked in China (9,46). Hence, monitoring the IADL and FL condition of the older people to reduce the occurrence of adverse events is an important recommendation to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The older people with FL were limited on physical activities, increasing the risk of disabled IADL, which greatly reduced the health status of the older people. IADL is an important indicator that affects health, but its impact on the health or death of the older people is often overlooked in China (9,46). Hence, monitoring the IADL and FL condition of the older people to reduce the occurrence of adverse events is an important recommendation to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…were in rural. 27 The sleep quality assessment survey found that 47% of adults and 70% elderly have sleep disorders. 28 The overall prevalence of diabetes in adults is 11.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of this study was that it was conducted in a nationwide community-based older Chinese adult sample with a long follow-up period, which can lead to better accuracy in the estimation of changes in multimorbidity 35 . However, some limitations should be noted.…”
Section: Discussionmentioning
confidence: 99%